Review on the theory of attractive quality kano model - Seder, Amin M. F.; Al Hazza, Muataz Hazza Faizi (Design for Scientific Renaissance, 2014)
Customer satisfaction is the critical factor that decided the success or failure of the new product or the new service. However, fulfilling the individual product requirements to a great extent does not necessarily imply a high level of customer satisfaction. Kano’s model is a methodology that helps in determining the different influences on new products and services. This paper also demonstrates how the results of a customer survey can be interpreted and how conclusions can be drawn and used for the management of customer satisfaction is demonstrated. A new product or new service can survive and become effective only if the customers are willing to buy. Kano Model is an insightful representation of 3 main categories of needs any product or service must address in order to survive in a competitive market. Kano model should be supported by quantitative approach that can strengthen the method by developing measured values to reduce the risk usually associated with developing new products and new services. Finally, the technical issue and cost estimation and market place situation will always the critical and key factor in any future decision making. Therefore Kano model should be done and implemented by a cross functional team with different expertise to minimize risk and optimize the results